2006
DOI: 10.1016/j.marpolbul.2006.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Survival under chronic stress from sediment load: Spatial patterns of hard coral communities in the southern islands of Singapore

Abstract: Six reef sites were chosen along the west coast of the southern islands of Singapore, at an increasing distance from the densely populated metropolitan area, to study the spatial patterns of coral reef communities on the upper reef slope ( approximately 4m) and the associated environmental conditions. Chronic exposure to high sediment load was the most obvious form of anthropogenic stress. Recruitment rates on ceramic tiles were low (1.4+/-1.0-20+/-14.7 recruits m(-2) yr(-1)) but decreased towards the main isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(21 citation statements)
references
References 33 publications
1
19
1
Order By: Relevance
“…Clearly, size was a key determinant of post-transplantation survival. However, the average post-transplantation mortality rate of all P. damicornis juveniles in this study (46%) was higher than that reported from other studies (11–34%) [10], [11], [17], likely due to the high sediment levels in Singapore waters, which have been estimated to limit scleractinian recruitment to two individuals m −2 [45]. As was observed during monthly visits to the study site, most juvenile colonies were smothered by fine particulate sediment, with obvious damage to the coral tissue.…”
Section: Discussioncontrasting
confidence: 81%
“…Clearly, size was a key determinant of post-transplantation survival. However, the average post-transplantation mortality rate of all P. damicornis juveniles in this study (46%) was higher than that reported from other studies (11–34%) [10], [11], [17], likely due to the high sediment levels in Singapore waters, which have been estimated to limit scleractinian recruitment to two individuals m −2 [45]. As was observed during monthly visits to the study site, most juvenile colonies were smothered by fine particulate sediment, with obvious damage to the coral tissue.…”
Section: Discussioncontrasting
confidence: 81%
“…In the mid-1970s much of the reef flat surrounding Pulau Hantu was destroyed following a reclamation project which increased the island's land area from 0.024 to 0.12 km 2 [2]. Today, approximately 2.21 km 2 of intertidal reef flat remains [47]. Sedimentation rates on the reef slope often exceed 10 mg cm −2 d −1 [6], [48], [49], levels considered to be detrimental to the more sensitive species of coral [40].…”
Section: Methodsmentioning
confidence: 99%
“…A study in Palau refined this perspective: Acropora transplants (at least one year old) survived equally well near and far from land, yet naturally occurring adult Acropora were rare near land, suggesting that the first year of life may be the most vulnerable for Acropora (Golbuu et al, 2011). Juvenile assemblages differed but adults did not after high flooding in the Great Barrier Reef (Thompson et al, 2014), while reefs in Singapore demonstrate an opposite pattern (Dikou and van Woesik, 2006). Additional research may reconcile these findings and assist restoration efforts by suggesting species and lifehistory stages when outplants are most likely to survive nearshore (Ng et al, 2016).…”
Section: Species-specific Effectsmentioning
confidence: 99%